Evidence of viral dissemination and seasonality in a Mediterranean river catchment: Implications for water pollution management. (15th August 2015) - Rusiñol, Marta; Fernandez-Cassi, Xavier; Timoneda, Natàlia; Carratalà, Anna; Abril, Josep Francesc; Silvera, Carolina; Figueras, Maria José; Gelati, Emiliano; Rodó, Xavier; Kay, David; Wyn-Jones, Peter; Bofill-Mas, Sílvia; et al.
Abstract: Conventional wastewater treatment does not completely remove and/or inactive viruses; consequently, viruses excreted by the population can be detected in the environment. This study was undertaken to investigate the distribution and seasonality of human viruses and faecal indicator bacteria (FIB) in a river catchment located in a typical Mediterranean climate region and to discuss future trends in relation to climate change. Sample matrices included river water, untreated and treated wastewater from a wastewater treatment plant within the catchment area, and seawater from potentially impacted bathing water. Five viruses were analysed in the study. Human adenovirus (HAdV) and JC polyomavirus (JCPyV) were analysed as indicators of human faecal contamination of human pathogens; both were reported in urban wastewater (mean values of 10 6 and 10 5  GC/L, respectively), river water (10 3 and 10 2  GC/L) and seawater (10 2 and 10 1  GC/L). Human Merkel Cell polyomavirus (MCPyV), which is associated with Merkel Cell carcinoma, was detected in 75% of the raw wastewater samples (31/37) and quantified by a newly developed quantitative polymerase chain reaction (qPCR) assay with mean concentrations of 10 4  GC/L. This virus is related to skin cancer in susceptible individuals and was found in 29% and 18% of river water and seawater samples, respectively. Seasonality was only observed for norovirus genogroup II (NoV GGII), which was more abundant in cold months with levels up to 10 4  GC/L in river water. Human hepatitis E virus (HEV) was detected in 13.5% of the wastewater samples when analysed by nested PCR (nPCR). Secondary biological treatment (i.e., activated sludge) and tertiary sewage disinfection including chlorination, flocculation and UV radiation removed between 2.22 and 4.52 log10 of the viral concentrations. Climate projections for the Mediterranean climate areas and the selected river catchment estimate general warming and changes in precipitation distribution. Persistent decreases in precipitation during summer can lead to a higher presence of human viruses because river and sea water present the highest viral concentrations during warmer months. In a global context, wastewater management will be the key to preventing environmental dispersion of human faecal pathogens in future climate change scenarios. Highlights: Human adenoviruses are useful for indexing fecal contamination. The first study detecting and quantifying MCPyV in bathing water. The new MCPyV qPCR assay proved to be sensitive and specific. Seasonal NoV GGII patterns are observed in river, sea and waste water samples. Viral concentration may differ with future climate changes.